Behind the Stiff Upper Lip: War Narratives of Older Men with Dementia. (1st August 2013) - Capstick, Andrea; Clegg, David
<x xml:space="preserve">Abstract</x> The concept of the stiff upper lip stands as a cultural metaphor for the repression and figurative 'biting back' of traumatic experience, particularly in military contexts. For men born in the first half of the twentieth century, maintaining a stiff upper lip involved the ability to exert high levels of cognitive control over the subjective, visceral, and emotional domains of experience. In the most common forms of dementia, which affect at least one in five men now in their 80s and 90s, this cognitive control is increasingly lost. One result is that, with the onset of dementia, men who have in the intervening years maintained a relative silence about their wartime experiences begin to disclose detailed memories of such events, in some cases for the first time. This article draws on narrative biographical data from three men with late-onset dementia who make extensive reference to their experience of war. The narratives of Sid, Leonard, and Nelson are used to explore aspects of collective memory of the two World Wars, and the socially constructed masculinities imposed on men who grew up and came of age during those decades. The findings show that in spite of their difficulties with short-term memory, people with dementia can contribute rich data to cultural studies research. Some aspects of the narratives discussed here may also be considered to work along the line of the counter-hegemonic, offering insights into lived experiences of war that have been elided in popular culture in the post-War years.